2008
DOI: 10.1364/oe.16.002363
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroadband operation of a femtosecond optical parametric generator based on BiB_3O_6 in the near-IR

Abstract: Ultrabroadband optical parametric generation in the near-IR (approximately 135 THz, 1.15-2.4 microm) is demonstrated using bismuth triborate, BiB(3)O(6) (BIBO), in a collinear geometry. The white light continuum energy obtained with a single stage reached 15 microJ (internal conversion efficiency of approximately 7%). Integral pulse durations as short as 63 fs were derived from the recorded FROG traces, comparable to the 45 fs pulse duration of the 1 kHz Ti:sapphire regenerative amplifier used for pumping at 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In order to meet the conditions discussed above, we selected BIBO as an OPA crystal because BIBO has its zero GDD wavelength at 1580 nm for an ordinary wave polarized along the y-axis, 21,22) which is advantageous for 790 nm pump pulses produced from Ti:sapphire lasers. We simulate an OPA gain (red dashed line in Fig.…”
mentioning
confidence: 99%
“…In order to meet the conditions discussed above, we selected BIBO as an OPA crystal because BIBO has its zero GDD wavelength at 1580 nm for an ordinary wave polarized along the y-axis, 21,22) which is advantageous for 790 nm pump pulses produced from Ti:sapphire lasers. We simulate an OPA gain (red dashed line in Fig.…”
mentioning
confidence: 99%
“…In this study, we choose a degenerate OPA combined with the unique characteristics of bismuth triborate (BiB 3 O 6 , BIBO) crystal when it is pumped by a Ti:sapphire chirpedpulse-amplification (CPA) laser. The advantages of this combination are described elsewhere [36][37][38][39]. Briefly, in this configuration, the central wavelength of the signal wave (1.6 μm) is set to ∼1.58 μm, where the group delay dispersion of BIBO crystal becomes zero.…”
Section: Ultrabroadband Parametric Gain Of Bibo Pumped By a Ti:sapphi...mentioning
confidence: 99%
“…where Δω and Δk 0 denote an offset from the central angular frequency of the signal wave and the phase mismatch at the central angular frequency, which can be eliminated by angle tuning. Among many types of OPA such as noncollinearlyphase-matched OPAs [7] and frequency domain OPAs [24], in the IR spectral region, it has been found that a unique solution to achieve broadband parametric amplification exists in a degenerate OPA when the central wavelength of the signal wave is equal to the zero group delay dispersion (GDD) wavelength of nonlinear crystals [25][26][27]. In a degenerate OPA, all the odd terms in equation ( 1) vanish because the central angular frequencies of the signal and idler are identical.…”
Section: Ultrabroadband Ir Opa Based On Bibo Crystalsmentioning
confidence: 99%